Effects of Ambon Banana Juice on Glucose Levels and Lipid Profile in Diabetic Rats - Herviana, Herviana; Indarto, Dono; Wasita, Brian (Universitas Aisyah Pringsewu, 2022)
Consumption of fruit juice is an alternative for diabetic patients who cannot consume fresh. Banana is one of the recommended fruits for diabetic patients because it has flavonoid content. This study aims to evaluate the effect of Ambon banana juice on fasting blood glucose (FBG), triglycerides, and total cholesterol levels in diabetic Wistar rats. The type of research is an experimental laboratory study with a pre-posttest design. The research sample was 21 male Wistar rats divided into 3 groups, T1 (control), T2 (10% fructose), and T3 (4 ml of Ambon banana juice) which were administered for 21 days. The FBG, triglycerides, and total cholesterol levels were examined using the colourimetric enzymatic method. The data were analyzed using one-way ANOVA, and post hoc tests. Ambon banana juice can improve FBG levels compared to control (p less than 0.01). Ambon banana juice can increase triglyceride levels but is significantly different from T2 (p less than 0.01). Ambon banana juice did not significantly increase total cholesterol levels compared to T2 (p less than 0.01). In conclusion, Ambon banana juice was demonstrated to decrease FBG and did not increase triglyceride and total cholesterol levels.Konsumsi jus buah merupakan alternatif bagi penderita diabetes yang tidak dapat mengkonsumsi buah segar. Pisang termasuk jenis buah yang direkomendasikan penderita diabetes, karena memiliki senyawa flavonoid. Tujuan penelitian ini untuk mengevaluasi efek jus pisang Ambon terhadap glukosa darah puasa (GDP), kadar trigliserida dan kolesterol total pada tikus diabetes. Jenis penelitian yaitu eksperimental laboratorik dengan desain pre-post test. Sampel penelitian berjumlah 21 ekor wistar jantan yang dibagi dalam 3 kelompok, T1 (kontrol), T2 (10% fruktosa), dan T3 (4ml jus pisang Ambon) yang diberikan selama 21 hari. Kadar GDP, trigliserida dan kolesterol total diukur menggunakan metode kolorimetri enzimatik. Data dianalisis menggunakan one-way ANOVA dan tes post hoc. Jus pisang ambon dapat membantu menurunkan kadar GDP dibanding kontrol (p kurang dari 0,01). Jus pisang Ambon dapat meningkatkan kadar trigliserida tetapi signifikan berbeda dibanding T2 (p kurang dari 0,01). Jus pisang ambon tidak signifikan meningkatkan kadar kolesterol total dibanding T2 (p kurang dari 0,01). Oleh karena itu, jus pisang ambon dapat membantu menurunkan kadar GDP dan tidak meningkatkan kadar trigliserida dan kolesterol total.